Determinants of Entrepreneurial Decision-Making: The Roles of E-Commerce, Digital Payment, Self-Efficacy, Accounting Information Systems, and Financial Literacy - Maharani, Safira Amelia; Fauzan (University of Darussalam Gontor, 2025)
The objective of this study is to analyze the influence of e-commerce, digital payment systems, self-efficacy, accounting information systems, and financial literacy on entrepreneurial decision-making. This analysis will be based on a case study of Accounting students at Universitas Muhamadiyah Surakarta from the class of 2021–2023. The present study employs a quantitative approach, utilizing proportionate stratified random sampling for the selection of the study's sample. The sample consists of 313 respondents. The primary data were collected through a digital questionnaire distributed via Google Forms, utilizing a 5-point Likert scale. The data were analyzed using Partial Least Squares (PLS) and processed with SmartPLS 4.1 software. The findings suggest that e-commerce, digital payment methods, and self-efficacy exert a positive and significant influence on entrepreneurial decision-making processes. Conversely, the accounting information system does not demonstrate a substantial impact on entrepreneurial decision-making.